ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. UNILEVER INDONESIA TBK TAHUN 2018-2022 - Maharani, Fira; Irvan Yoga Pardistya (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2024)
Every company needs financial statements as a reference for decision making related to its company's financial performance. This study aims to determine the financial performance of PT. Unilever Indonesia Tbk from 2018 to 2022 analyzed using financial ratios, including Liquidity, Solvency, Profitability and Activity ratios. This research uses secondary data obtained from the financial statements of PT. Unilever Indonesia Tbk. Quantitative descriptive analysis method is used to describe the company's financial ratios. The results of the data analysis show that the company's liquidity level is said to be good, measured by a current ratio that is always above 1. The level of solvency has increased, measured using a debt to ratio that shows the company is able to meet its long-term obligations. In contrast to the level of profitability, which is measured using net profit margin, return on assets, and return on equity shows a downward trend means that the company's profitability is not good. Activity level, measured by total asset turnover. The results show a steady trend which means the company is quite efficient in rotating its assets.